2005
DOI: 10.1021/bi048061n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nucleosomes Consisting of the Human Testis/Sperm-Specific Histone H2B Variant (hTSH2B)

Abstract: We have reported earlier the occurrence of a specific histone H2B variant in human testis and sperm. Here we have structurally characterized this protein, its association with the rest of the histone octamer, and its effects on the nucleosome structure. We show that a reconstituted octamer consisting of hTSH2B and a stoichiometric complement of histones H2A, H3, and H4 exhibits a lower stability compared to the reconstituted native counterpart consisting of H2B. In contrast, the hTSH2B containing octamers are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 51 publications
5
52
1
1
Order By: Relevance
“…These facts suggested that TSH2B may form an unstable nucleosome for enhanced histone-protamine exchange. Consistently, previous biochemical experiments revealed that human TSH2B does not form a stable histone octamer, although the stabilities of the TSH2B and canonical H2B nucleosomes are similar (Li et al, 2005).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…These facts suggested that TSH2B may form an unstable nucleosome for enhanced histone-protamine exchange. Consistently, previous biochemical experiments revealed that human TSH2B does not form a stable histone octamer, although the stabilities of the TSH2B and canonical H2B nucleosomes are similar (Li et al, 2005).…”
Section: Introductionsupporting
confidence: 87%
“…4c,4d,4e,4f,4g,4h,4i and 4j). A previous biochemical study revealed that human TSH2B forms an unstable histone octamer with chicken H2A, H3 and H4 (Li et al, 2005). The water-mediated hydrogen bonds between H2B Asn84 and H4 Arg78 in the canonical nucleosome are not formed in the TSH2B nucleosome.…”
Section: Crystallization and Determination Of The Tsh2b Nucleosome Stmentioning
confidence: 92%
“…A possible human counterpart of H2AL2, H2A.Bbd, which is highly expressed in the testis, was also suggested to form a specific nucleosome structure with reduced stability (22)(23)(24). Furthermore, nucleosomes containing a testis-specific H2B variant, hTSH2B/TH2B, were reportedly unstable, as compared to the conventional nucleosome (25). Therefore, the instability of these nucleosomes formed by the testis-specific histone variants may be a common property required for chromatin reorganization during spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6][7] Histone variants incorporate into nucleosomes just like canonical histones and the structure of variant nucleosomes is often very similar to that of canonical nucleosomes. 8 Despite that, these molecules clearly have functions that are genetically distinct from canonical histones.…”
Section: Random Deposition Of Histone Variantsmentioning
confidence: 99%